Use of metformin for the treatment of acne in the absence of polycystic ovarian syndrome: a literature review - Ana M. Jesus; Ana S. Ribeiro; Catarina Cunha-Santos; Joana F. Ferreira; Mafalda Freitas-Osório; Sílvia Ribeiro-Almeida; Jorge Andrade; Teresa Leal-Pinto; Jacinta Coelho; Diana Bernardo (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Acne is a chronic, inflammatory, multifactorial disorder of the pilosebaceous unit, with no associated mortality but often accompanied by high physical and psychological morbidity. Metformin is an antihyperglycemic drug under investigation as a therapeutic option for acne in adults and adolescents. The authors performed an evidence-based review, according to the population, intervention, control, and outcomes methodology, to assess whether there is evidence for the use of metformin (monotherapy or adjuvant) in the treatment of acne in adolescents and adults in the absence of polycystic ovary syndrome (PCOS). At the end of the review method, five original studies were eligible for this review. All studies showed a statistically significant improvement in acne lesions in patients receiving metformin. Despite the small number of articles included in this review, results suggest that the use of metformin for the management of acne can be an option, although further investigation is required. According to the current evidence, metformin could be a therapeutic option in the treatment of acne without PCOS, with strength of recommendation taxonomy B level of evidence. This treatment has shown clinical benefits, particularly in acne resistant to other therapies or in more severe acne cases, improving the number and severity of the lesions.